Recent Progress on Critical Cleaning of Sapphire Single-Crystal Substrates: A Mini-Review - Zhang, Dan; Gan, Yang (Recent Patents on Chemical Engineering, 2013)
Sapphire single-crystals are one of the industrial favorite substrates for GaN film deposition and LED application as well as a model system for oxides’ aqueous interfacial chemistry studies. Contamination control of sapphire substrates is critical to the device fabrication and experimental studies of interfacial properties. Here we reviewed various methods reported in the literature including conventional and new wet-chemical methods, and UV/plasma methods. Special attentions were paid to their cleaning performance in terms of reliably removing organic/particulate/heavy metallic contaminants.
Keywords: Surface structure